phân tích thành nhân tử a) x mũ 4 – 4x ² +4x -1 b) a(b ² – c ²)+b(c ²- a ²) +c(a ² – b ²) c) x mũ 4 +4 20/07/2021 Bởi Reagan phân tích thành nhân tử a) x mũ 4 – 4x ² +4x -1 b) a(b ² – c ²)+b(c ²- a ²) +c(a ² – b ²) c) x mũ 4 +4
Đáp án: a, `x^4 – 4x^2 + 4x – 1` ` = (x^4 – 1) – (4x^2 – 4x)` `= (x^2 – 1)(x^2 + 1) – 4x.(x – 1)` `= (x – 1)(x + 1)(x^2 + 1) – 4x(x – 1)` `= (x – 1)(x^3 + x^2 + x + 1 – 4x)` `=(x – 1)(x^3 + x^2 – 3x + 1)` `= (x – 1)[(x^3 + 2x^2 – x) – (x^2 + 2x – 1)]` `= (x – 1)[x.(x^2 + 2x – 1) – (x^2 + 2x – 1)]` `=(x – 1)(x – 1)(x^2 + 2x – 1)` `= (x – 1)^2 . (x^2 + 2x – 1)` b, `a(b^2 – c^2) + b(c^2 – a^2) + c(a^2 – b^2)` ` = a(b^2 – c^2) + bc^2 – ba^2 + ca^2 – cb^2` ` = a(b^2 – c^2) – (cb^2 – bc^2) – (ba^2 – ca^2)` `= a(b – c)(b + c) – bc.(b – c) – a^2 . (b – c)` ` = (b – c)(ab + ac – bc – a^2)` `=(b – c)[(ac – bc) – (a^2 – ab)]` `=(b – c)[c.(a – b) – a.(a – b)]` `=(b – c)(c – a)(a – b)` c, `x^4 + 4` ` = (x^4 + 4x^2 + 4) – 4x^2` `= (x^2 + 2)^2 – (2x)^2` `= (x^2 – 2x + 2)(x^2 + 2x + 2)` Giải thích các bước giải: Bình luận
Đáp án: a/ $(x-1)^2(x+1+\sqrt{2})(x+1-\sqrt{2})$ b/ $(a-b)(b-c)(c-a)$ c/ $(x^2+2+2x)(x^2+2-2x)$ Giải thích các bước giải: a/ $x^4-4x^2+4x-1$ $=x^4-(4x^2-4x+1)$ $=x^4-(2x-1)^2$ $=(x^2-2x+1)(x^2+2x-1)$ $=(x-1)^2[(x^2+2x+1)-2]$ $=(x-1)^2[(x+1)^2-2]$ $=(x-1)^2(x+1+\sqrt{2})(x+1-\sqrt{2})$ b/ $a(b^2-c^2)+b(c^2-a^2)+c(a^2-b^2)$ $=ab^2-ac^2+bc^2-a^2b+a^2c-b^2c$ $=(ab^2-a^2b)-(ac^2-bc^2)+(a^2c-b^2c)$ $=-ab(a-b)-c^2(a-b)+c(a^2-b^2)$ $=-ab(a-b)-c^2(a-b)+c(a-b)(a+b)$ $=(a-b)(-ab-c^2+ac+bc)$ $=(a-b)[-(ab-ac)+(bc-c^2)]$ $=(a-b)[-a(b-c)+c(b-c)]$ $=(a-b)(b-c)(c-a)$ c/ $x^4+4$ $=x^4+4x^2+4-4x^2$ $=(x^2+2)^2-4x^2$ $=(x^2+2+2x)(x^2+2-2x)$ Bình luận
Đáp án:
a, `x^4 – 4x^2 + 4x – 1`
` = (x^4 – 1) – (4x^2 – 4x)`
`= (x^2 – 1)(x^2 + 1) – 4x.(x – 1)`
`= (x – 1)(x + 1)(x^2 + 1) – 4x(x – 1)`
`= (x – 1)(x^3 + x^2 + x + 1 – 4x)`
`=(x – 1)(x^3 + x^2 – 3x + 1)`
`= (x – 1)[(x^3 + 2x^2 – x) – (x^2 + 2x – 1)]`
`= (x – 1)[x.(x^2 + 2x – 1) – (x^2 + 2x – 1)]`
`=(x – 1)(x – 1)(x^2 + 2x – 1)`
`= (x – 1)^2 . (x^2 + 2x – 1)`
b, `a(b^2 – c^2) + b(c^2 – a^2) + c(a^2 – b^2)`
` = a(b^2 – c^2) + bc^2 – ba^2 + ca^2 – cb^2`
` = a(b^2 – c^2) – (cb^2 – bc^2) – (ba^2 – ca^2)`
`= a(b – c)(b + c) – bc.(b – c) – a^2 . (b – c)`
` = (b – c)(ab + ac – bc – a^2)`
`=(b – c)[(ac – bc) – (a^2 – ab)]`
`=(b – c)[c.(a – b) – a.(a – b)]`
`=(b – c)(c – a)(a – b)`
c, `x^4 + 4`
` = (x^4 + 4x^2 + 4) – 4x^2`
`= (x^2 + 2)^2 – (2x)^2`
`= (x^2 – 2x + 2)(x^2 + 2x + 2)`
Giải thích các bước giải:
Đáp án:
a/ $(x-1)^2(x+1+\sqrt{2})(x+1-\sqrt{2})$
b/ $(a-b)(b-c)(c-a)$
c/ $(x^2+2+2x)(x^2+2-2x)$
Giải thích các bước giải:
a/ $x^4-4x^2+4x-1$
$=x^4-(4x^2-4x+1)$
$=x^4-(2x-1)^2$
$=(x^2-2x+1)(x^2+2x-1)$
$=(x-1)^2[(x^2+2x+1)-2]$
$=(x-1)^2[(x+1)^2-2]$
$=(x-1)^2(x+1+\sqrt{2})(x+1-\sqrt{2})$
b/ $a(b^2-c^2)+b(c^2-a^2)+c(a^2-b^2)$
$=ab^2-ac^2+bc^2-a^2b+a^2c-b^2c$
$=(ab^2-a^2b)-(ac^2-bc^2)+(a^2c-b^2c)$
$=-ab(a-b)-c^2(a-b)+c(a^2-b^2)$
$=-ab(a-b)-c^2(a-b)+c(a-b)(a+b)$
$=(a-b)(-ab-c^2+ac+bc)$
$=(a-b)[-(ab-ac)+(bc-c^2)]$
$=(a-b)[-a(b-c)+c(b-c)]$
$=(a-b)(b-c)(c-a)$
c/ $x^4+4$
$=x^4+4x^2+4-4x^2$
$=(x^2+2)^2-4x^2$
$=(x^2+2+2x)(x^2+2-2x)$